The New South Wales Institute of Sports
Website of the New South Wales Institute of Sports. The NSW Institute of Sport (NSWIS), located at Sydney Olympic Park, was established as a statutory body under the Institute of Sport Act, 1995 following a review recommending central coordination and monitoring of high performance sports programs. Operations officially commenced in 1996. Today the Institute has over 700 high performance athletes on squad or individual scholarships and offers 31 sport programs across 24 sports. Under our innovative Mobile/Regional program, the NSWIS offers a comprehensive spectrum of support services to NSWIS athletes in their home environment, enabling them to pursue their sporting careers with minimal disruption to their family, education and employment. The Institute`s Principal Partner is ClubsNSW, who provides $1 million a year in sponsorship support. The NSWIS Purpose: The NSWIS is a leading high performance sport Institute that provides world class coaching, services, and flexible innovative training environments. In conjunction with a holistic approach to athlete welfare, career and educational assistance the NSWIS supports and develops targeted elite and emerging athletes to achieve their highest potential.